The Human Library and the development of cultural awareness and sensitivity in occupational therapy students: a mixed methods study - Pope, Kirsty; Hewlin-Vita, Heather; Chu, Eli Mang Yee (Frontiers in Medicine, 2023)
Introduction:[blinded for review] university in Australia has adopted the Human Library as a teaching activity aimed at enhancing occupational therapy (OT) students' cultural awareness and sensitivity; however, its effect on cultural competence in healthcare profession students has not been previously investigated.To examine whether participation in a Human Library can facilitate the development of OT students' cultural awareness and sensitivity and to understand the factors contributing to changes in cultural competence from the students' perspective.This is a mixed-method study. Quantitative data was collected by participant characteristic survey and pre/post-Human Library Cultural Competence Assessment (CCA). The quantitative data was used to inform the selection of participants and questions for the second qualitative phase. Quantitative data were analyzed using independent samples and paired t-tests, analysis of variance and Pearson correlation. Qualitative data were analyzed using coding reliability thematic analysis.Statistically significant increases were noted in CAS, CCB and overall CCA scores from pre-to post-Human Library. Participant characteristics such as gender, work experience in aged care and the health sector had a positive effect on pre-Human Library CCA results. Qualitative data demonstrated that participants perceived they had a level of cultural competence prior to attending the Human Library however, still made gains in cultural awareness and sensitivity and were motivated and inspired to provide culturally congruent healthcare.The Human Library can be considered for inclusion within a suite of learning methods for healthcare professional student curricula as a cost-effective, flexible teaching method for the development of competencies for culturally congruent healthcare.